Dynamics Analysis and Simulation of the Pressure Mechanism of Bronzing Machine based on Matlab - Chai Sanzhong; Qiu Jiuan (Jixie chuandong)
Neglecting the clearance and friction in the kinematic pair,the rigid body dynamics analysis of bronzing machine pressure mechanism is carried out,the mathematical model is established.By using the Matlab,the dynamics procedure of mechanism is compiled and calculated,the simulation curve of the main component is drawn,the simulation curves of no-load and load of two conditions are compared,and the force analysis of the pressure mechanism is carried out.